2007
DOI: 10.1086/516728
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Delayed Detonation, Asymmetry, and Electron Capture in the Mid‐Infrared Spectra of Supernovae 2003hv and 2005df

Abstract: We present mid-infrared (5.2Y15.2 m) spectra of the Type Ia supernovae (SNe Ia) 2003hv and 2005df observed with the Spitzer Space Telescope. These are the first observed mid-infrared spectra of thermonuclear supernovae, and show strong emission from fine-structure lines of Ni, Co, S, and Ar. The detection of Ni emission in SN 2005df 135 days after the explosion provides direct observational evidence of high-density nuclear burning forming a significant amount of stable Ni in a SN Ia. The SN 2005df Ar lines als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(167 citation statements)
references
References 51 publications
7
154
1
Order By: Relevance
“…This assumption is supported by a variety of studies; the spectrum synthesis calculations of a time series of spectra obtained during t = 5-377 days for SN 2002bo, SN 2004eo, and SN 2003du demonstrated that the abundance distributions in the ejecta of these SNe Ia are fully stratified with some degree of macroscopic mixing (Stehle et al 2005;Mazzali et al 2008;Tanaka et al 2011). Based on the analysis of the emission profiles in the mid-IR spectrum at t 135 days, Gerardy et al (2007) have also shown that the ejecta structure in SN Ia 2005df is chemically stratified. Furthermore, X-ray observations of the Tycho SNR indicate that the layered composition has been retained in the ejecta even at ∼450 yr after the explosion (Badenes et al 2006;Hayato et al 2010; see also Kosenko et al 2010 for Type Ia SNR 0519-69.0).…”
Section: Model Of Sne Iamentioning
confidence: 77%
See 1 more Smart Citation
“…This assumption is supported by a variety of studies; the spectrum synthesis calculations of a time series of spectra obtained during t = 5-377 days for SN 2002bo, SN 2004eo, and SN 2003du demonstrated that the abundance distributions in the ejecta of these SNe Ia are fully stratified with some degree of macroscopic mixing (Stehle et al 2005;Mazzali et al 2008;Tanaka et al 2011). Based on the analysis of the emission profiles in the mid-IR spectrum at t 135 days, Gerardy et al (2007) have also shown that the ejecta structure in SN Ia 2005df is chemically stratified. Furthermore, X-ray observations of the Tycho SNR indicate that the layered composition has been retained in the ejecta even at ∼450 yr after the explosion (Badenes et al 2006;Hayato et al 2010; see also Kosenko et al 2010 for Type Ia SNR 0519-69.0).…”
Section: Model Of Sne Iamentioning
confidence: 77%
“…Höflich et al (1995) Taubenberger et al (2011) have reported probable detection of CO emission at ∼85 days after the peak brightness in superluminous SN Ia 2009dc. We also note that the possible formation of SiO molecules is supposed for SN Ia 2005df, but the formation efficiency would be extremely low ( 0.01%; Gerardy et al 2007).…”
Section: Formation Of Co and Sio Moleculesmentioning
confidence: 84%
“…Very few observations at wavelengths outside the optical and near-infrared window have been obtained. Only two events have so far been observed in the thermal infrared, SN 2003hv and SN 2005df (Gerardy et al 2007). The detection of emission lines of nickel and cobalt over 100 days after explosion indicates a surprisingly large amount of stable nickel in the ejecta.…”
Section: Type Ia Supernovaementioning
confidence: 99%
“…-The synthesis of intermediate-mass elements is scarce (see García-Senz et al 2007). -The ejecta are not chemically stratified, as demanded by observations of supernovae and remnants (Badenes et al 2006;Gerardy et al 2007). -Large clumps of radioactive 56 Ni and 56 Co are present at the photosphere at the time of maximum brightness.…”
Section: Introductionmentioning
confidence: 99%